(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information on the growth of Bracteococcus bullatus belonging to the Chlorophyta division in different nutrient media, the composition of nutrient media, the cell structure of Bracteococcus bullatus, and the distribution areas of Bracteococcus bullatus in the eroded soils of the Fergana Valley. Analyzes of the results shown in several nutrient environments are presented. The obtained results showed that Bracteococcus bullatus species of algae grew well enough in Bristol and BG11+ mediums, and the expected biomass was formed. The formation of thousands of cells was also effectively achieved in these nutrient media.